1999
DOI: 10.1007/s007050050631
|View full text |Cite
|
Sign up to set email alerts
|

Liver and peripheral blood mononuclear cells are not major sites for GB virus-C/hepatitis G virus replication

Abstract: The pathogenesis and replication sites of GB virus-C/hepatitis G virus (GBV-C/HGV) in humans remain unclear. The presence of GBV-C/HGV and hepatitis C virus (HCV) RNA sequences in matched serum, peripheral blood mononuclear cells (PBMC) and liver samples in 10 patients with GBV-C/HGV infection, 8 of whom were coinfected with HCV was explored. Positive- and negative-strand GBV-C/HGV and HCV RNA were detected by strand-specific reverse-transcription polymerase chain reaction (RT-PCR), and virus titers were quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The potential of HGV to cause hepatitis in humans is questionable. Controversial data exist concerning whether or not HGV replicates in the liver [3][4][5][6] . HGV is highly prevalent among population groups at risk of parenterally transmitted viral agents, but it has also a worldwide distribution in other non-risk population groups.…”
mentioning
confidence: 99%
“…The potential of HGV to cause hepatitis in humans is questionable. Controversial data exist concerning whether or not HGV replicates in the liver [3][4][5][6] . HGV is highly prevalent among population groups at risk of parenterally transmitted viral agents, but it has also a worldwide distribution in other non-risk population groups.…”
mentioning
confidence: 99%
“…Recent data suggest that GBV-C:HGV may replicate in human peripheral blood mononuclear cells (PBMC) (70,71) and in endothelial cells (72). The ndings have, however, been questioned (73). So far knowledge of the tissuespeci c tropism and the major site of replication for GBV-C:HGV are limited.…”
Section: Tissue Tropismmentioning
confidence: 99%
“…Although GBV-C was suggested initially to be a hepatitis virus, subsequent studies indicated that majority of GBV-C-infected patients had no detectable evidence of hepatitis [Stapleton, 2003]. Furthermore, lines of evidence argued that GBV-C might not be a hepatotropic virus [Laskus et al, 1998;Kao et al, 1999]. On the other hand, TTV and SEN virus are both believed to be hepatotropic viruses.…”
Section: Introductionmentioning
confidence: 96%